Recent advances in antimultiple myeloma drug development. (May 2014) - Wang, Nuozhou; Bartlow, Patrick; Ouyang, Qin; Xie, Xiang-Qun
Multiple myeloma (MM) is the second most common hematological malignancy and is characterized by the aberrant proliferation of terminally differentiated plasma B cells with impairment in apoptosis capacity. Particularly, osteolytic bone diseases and renal failure resulting from hyperparaproteinemia and hypercalcemia have been the major serious sequelae that are inextricably linked with MM tumor progression. Despite the introduction of new treatment regimens, problematic neuropathy, thrombocytopenia, drug resistance and high MM relapse rates continue to plague the current therapies. New chemical agents are in development on the basis of understanding several signaling pathways and molecular mechanisms like tumor necrosis factor-α, proteasome, PI3K and MARKs. This review focuses on the most recent patents and clinical trials in the development of new medicine for the treatment of multiple myeloma. Furthermore, the important signaling pathways involved in the proliferation, survival and apoptosis of myeloma cells will be discussed.